2010
DOI: 10.1002/dvdy.22182
|View full text |Cite
|
Sign up to set email alerts
|

The function and regulation of TBX22 in avian frontonasal morphogenesis

Abstract: The frontonasal mass gives rise to the facial midline and fuses with the maxillary prominence to form the upper lip. Here we focus on the regulation and function of TBX22, a repressor dynamically expressed in the frontonasal mass. Both FGF and Noggin (a BMP antagonist) strongly induce gTBX22, however, each has opposite effects on morphogenesis -Noggin inhibits whereas FGF stimulates growth. To determine whether TBX22 mediates these effects, we used retroviruses to locally increase expression levels. RCAS::hTBX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 90 publications
5
21
0
Order By: Relevance
“…By stage 26, TBX22 expression in the developing palate becomes independent of FGF signaling, while it still responds to repression by BMP4. These findings are in line with the results of Higashihori et al (2010) who also showed that TBX22 expression in the chicken frontonasal mass is induced and maintained by FGF and negatively regulated by BMP signaling.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofsupporting
confidence: 92%
See 4 more Smart Citations
“…By stage 26, TBX22 expression in the developing palate becomes independent of FGF signaling, while it still responds to repression by BMP4. These findings are in line with the results of Higashihori et al (2010) who also showed that TBX22 expression in the chicken frontonasal mass is induced and maintained by FGF and negatively regulated by BMP signaling.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofsupporting
confidence: 92%
“…Nevertheless, the events downstream of these two pathways and their combined effects are so far only partially understood. A recent study by Higashihori et al (2010), published while this article was being assembled, demonstrated that TBX22 expression is regulated by both FGF and BMP pathways during development of the chicken frontonasal mass. Here we confirm their findings and, in addition, show that these two pathways also regulate TBX22 expression during development of the secondary palate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations